Cortical Auditory Deafferentation Induces Long-Term Plasticity in the Inferior Colliculus of Adult Rats: Microarray and qPCR Analysis - Clarkson, Cheryl; Herrero-Turrión, Manuel J.; Merchán, Miguel A. (Frontiers in Neural Circuits, 2012)
The cortico-collicular pathway is a bilateral excitatory projection from the cortex to the inferior colliculus (IC). It is asymmetric and predominantly ipsilateral. Using microarrays and RT-qPCR we analyzed changes in gene expression in the IC after unilateral lesions of the auditory cortex, comparing the ICs ipsi- and contralateral to the lesioned side. At 15 days after surgery there were mainly changes in gene expression in the IC ipsilateral to the lesion. Regulation primarily involved inflammatory cascade genes, suggesting a direct effect of degeneration more than a neuronal plastic reorganization. Ninety days after the cortical lesion the ipsilateral IC showed a significant up-regulation of genes involved in apoptosis and axonal regeneration combined with a down-regulation of genes involved in neurotransmission, synaptic growth and gap junction assembly. In contrast, the contralateral IC at 90 days post-lesion showed an up-regulation in genes primarily related to neurotransmission, cell proliferation and synaptic growth. There was also a down-regulation in autophagy and neuroprotection genes. These findings suggest that the reorganization in the IC after descending pathway deafferentation is a long-term process involving extensive changes in gene expression-regulation. Regulated genes are involved in many different neuronal functions, and the number and gene rearrangement profile seems to depend on the density of loss of the auditory cortical inputs.